Budgeting as practice and knowing in action: experimenting with Bourdieu's theory of practice: an empirical evidence from a public university - Chaturika Priyadarshani Seneviratne; Ashan Lester Martino (Asian Journal of Accounting Research, 2021)
The present study aims to explore how various doings, strategic actions and power relations stemming from internal agents are instrumental in (re)constituting the different forms and meanings of budgeting in a specific field.The paper uses a single-case study method based on a Sri Lankan public university. Data are collected using interviews, documentary evidence and observations.The empirical evidence suggested that internal agents are crucial, and they are the producers of budgetary practice as they possess practical knowledge and power relations in the field where they operate. The case data demonstrate that organisational agents do have real essence as active and acting to produce effects in budgeting practices, and the significance of exploring the singularity of multiple agents in terms of their viewpoints, trajectories, dispositions and power relations, who may form, sustain or interrupt budgetary practices in a given setting.As the research is directed towards the selection of in-depth enquiry of specific setting infused with culture, values, perception and ideology, it might cause to diminish the researcher's analytical objectivity and independence of the research.As budgetary practices are product of human interaction, it is important to note that practitioners should be concerned with what agents do in actual practice and their inactions, influences and power relations in budgeting practices, which might not align with the structural forces enlisted in the budgeting. It would be of interest for future empirical research to explore the interplay between the diverse interests of organisational agents and agents beyond the individual organisations.This study contributes to the literature on management control practices by documenting the importance of understanding the â€œpracticeâ€ through relational thinking of all three concepts is emphasised, such interrelated theoretical insights are seldom used to understand accounting practices. This research emphasises the importance of bringing out the microprocessual facets of management control to open up its non-conscious, non-strategic and non-rationalist forms.